(untitled) (KYAMC Journal, 2017)
A 33 years aged gentle lady from Uttara, Dhaka, got admitted through emergency with moderate to severe right sided flank pain.Contrast enhanced CT scan of whole abdomen revealed a 4x3 cm size retroperitoneal tumour. She was explored and found to have a rare disease—soft tissue tumour arising from right gonadal vessels. Histopathology confirmed it as leiomyosarcoma of the right ovarian vein. Patient had post surgical smooth recovery. venous leiomyosarcomas are rare tumour that to from ovarian vein. Clinicopathological features, treatment and follow up of this case are discussed here. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 431-433